Buckling of Arctic Sea Ice in Lateral Compression. - Dugan, John (1997)
Sea ice can fail under lateral compression by buckling, a form of flexural motion, and this is thought to be a common phenomenon during pressure ridging. This type of motion is modeled as a stability problem for the vibration of a thin plate over water which is excited by ambient motions while the plate is under compression. The plate has an 'effective' bending modulus to account for actual depth varying modulus of elasticity of the ice. The dispersion relation for the flexural vibrations is evaluated, and explicit formulas are found for the critical value of compressive stress causing failure and for the most unstable wavelength. The critical compressive stress is about 1,000,000 N/m2 for 10 cm thick first-year ice and slightly less than l0,000,000 N/m2 for 3 m thick multi-year ice. An experimental technique for evaluating the effective bending modulus and the critical compressive stress is suggested, namely, by measurement of the dispersion curve for free flexural waves which are omnipresent in Arctic pack ice. Photographic evidence of pre-buckling flexure is provided for an example case on a refrozen lead.